Soil Use Legacy as Driving Factor for Soil Erosion under Conservation Agriculture - Grahmann, Kathrin; Rubio, Valentina; Perez-Bidegain, Mario; Quincke, Juan Andrés (Frontiers in Environmental Science, 2022)
Water erosion can cause irreversible depletions in soil quality and crop productivity. The susceptibility of the soil to soil erosion is defined by current and historical management practices. Historical soil management practices, like ploughing or subsoil loosening may lead to irreversible degradations of soils, which in turn increases soil erosion risk. Six “Wischmeier” plots under conservation agriculture, but with different historic treatments regarding soil use and management, were evaluated. These plots were installed in 1984 in Uruguay on a Vertic Argiudoll. The objective of this study was to quantify how changes in soil quality generated by different historical soil use and management since the 1980s, contribute to current runoff and soil erosion in a cropping system under soil conservation practices using no-till, residue retention and cover crops. Considering differences in land use legacy, plots were classified in three categories with contrasting historic agricultural intensification index (IAI). The IAI was developed combining the duration of land use under agricultural production and the number and intensity of tillage activity resulting in the treatments: tillage with crop-pasture rotation (TIL_CP), no-tillage under several rotations (NT_Mix) and tillage with continuous cropping (TIL_CROP) with an increasing IAI of 3.5, 7.1 and 11.8, respectively. Rainfall events, runoff water and total, fixed and volatile solids were studied from 2017 to 2019. Several soil physical and soil chemical properties were measured during 2019 in all plots. Yearly average runoff amounted 209, 579 and 320 mm in 2017, 2018 and 2019, respectively. Yearly average soil losses were 233, 805 and 139 kg/ha with significant differences among years. Lowest soil losses were observed in TIL_CP with lowest IAI. Infiltration rate was lowest in plots with highest IAI. Soil bulk density was highest (1.3 g/cm3) in plots with high IAI. SOC and PMN were lowest in TIL_CROP, holding the highest IAI. Conservation agriculture minimized soil erosion losses in all plots and years, and erosion was much lower than the maximum tolerable threshold of 7000 kg/ha for this particular soil. However, in historically intensively tilled and cropped soils, soil quality showed long-term adverse effects pointing towards a reduced resilience of the agricultural system.